Reply to Panero: Robust phylogenetic placement of fossil pollen grains: the case of Asteraceae - Barreda, Viviana Dora; Palazzesi, Luis; Telleria, María Cecilia; Olivero, Eduardo Bernardo; Raine, J. Ian; Forest, Félix (Proceedings of the National Academy of Sciences)
We thank Panero for his interest in our paper. However, we consider his interpretations somewhat incomplete and misleading, principally because he reports results using methods that we did not apply in our study, and underestimates the importance of pollen morphological characters in phylogenetic studies. We respond to each of these points with the aim of clarifying his misinterpretations about our paper. Fil: Barreda, Viviana Dora. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Palazzesi, Luis. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina. Royal Botanic Gardens; Reino Unido Fil: Telleria, María Cecilia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Laboratorio de Sistemática y Biología Evolutiva; Argentina Fil: Olivero, Eduardo Bernardo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Raine, J. Ian. GNS Science. Department of Paleontology; Nueva Zelanda Fil: Forest, Félix. Royal Botanic Gardens; Reino Unido